Cordero: il giurista - Maddalena, Marcello (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2024)
The paper describes the profile of Franco Cordero as jurist through a personal reconstruction of the memories of Marcello Maddalena (a former student of Cordero’s), by valuing his rich intellectual profile.